1996
DOI: 10.2527/1996.74112687x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary neutral detergent fiber on ileal digestibility and portal flux of nitrogen and amino acids and on nitrogen utilization in growing pigs.

Abstract: Two experiments were conducted to determine the effects of dietary NDF on apparent ileal and fecal digestibility and portal flux of nitrogen (N) and amino acids, and on N retention in growing pigs. In four equal portions (at 0600, 1200, 1800, and 2400) barrows on Treatment B received a basal diet, based on casein, cornstarch, and dextrose, at a feeding level of 2.6 times energy for maintenance. Barrows on Treatment B+NDF received an additional amount of 15% (wt/wt) of purified wheat bran NDF (pNDF). In Exp. 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
45
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 50 publications
15
45
0
1
Order By: Relevance
“…Among the chemical components, NDF provided the best estimate thanks to a highly predictable negative linear relationship (Table 2). These results are in agreement with the existing literature (Lenis et al, 1996;Dilger et al, 2004). Dilger et al (2004) also found various linear reductions of the EAA SID of SBM with progressive inclusion of soy hulls.…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential supporting
confidence: 93%
“…Among the chemical components, NDF provided the best estimate thanks to a highly predictable negative linear relationship (Table 2). These results are in agreement with the existing literature (Lenis et al, 1996;Dilger et al, 2004). Dilger et al (2004) also found various linear reductions of the EAA SID of SBM with progressive inclusion of soy hulls.…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential supporting
confidence: 93%
“…In studies on pigs fed purified diets containing NDF from wheat, ileal protein digestibility decreased by 4.9 percentage units when 18% NDF was included (Schulze et al, 1994). A similar effect was observed by Lenis et al (1996) in pigs fed a diet containing 15% NDF. In a recently published paper, Fan et al (2001) evaluated the effect of NDF content on apparent ileal amino acid digestibility in six high-protein wheat samples given to growing-finishing pigs.…”
Section: Itemsupporting
confidence: 53%
“…It has been well established that dietary NDF has direct adverse effects on apparent ileal CP and AA digestibility in pigs. It was shown that the dietary inclusion of water-insoluble fiber depressed the apparent ileal digestibility values of CP and AA (Graham et al 1986;Li et al 1994;Schulze et al 1994;Lenis et al 1996). The lower ileal digestibility values of CP and AA with increasing water-insoluble fiber content may be attributed to an increase in the rate of passage of digesta (Stanogias and Pearce 1985) and increased distal ileal losses of endogenous CP and AA (Sauer et al 1977;Taverner et al 1981;De Lange et al 1989;Furuya and Kaji 1992;Leterme et al 1992).…”
Section: Resultsmentioning
confidence: 99%